Nonlocal boundary-value problem for parabolic equations - Zadorozhna, N. M.; Mel'nyk, O. M.; Ptashnik, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We study the problem for Shilov parabolic equations of arbitrary order with constant coefficients with conditions nonlocal in time and periodic in space variables. We establish conditions for the existence and uniqueness of a classical solution of the problem and prove metric theorems on lower bounds of small denominators appearing in the construction of a solution of the problem.